Fundamentals of School Scheduling - Schroth, Gwen; Pankake, Anita M.; Terry, Paul (Rowman & Littlefield Publishers, 1997)
School administrators must constantly evaluate and refine school scheduling for optimum student and teacher performance. This book is for school administrators who need appropriate management techniques for scheduling students into classes. All parts of the puzzle are presented so the administrator can make wise choices about configuring the school day. Discusses a variety of scheduling formats—traditional, block, and team models—but no one type is advocated. Essential for new principals or administrators planning to change scheduling formats, and principals moving between elementary and secondary levels.